The Adductor Sling Technique for Pediatric Medial Patellofemoral Ligament Reconstruction Better Resists Dislocation Loads When Compared With Adductor Transfer at Time Zero in a Cadaveric Model - George C. Balazs, M.D; Kathleen N. Meyers, M.S; Elizabeth R. Dennis, M.D; Suzanne A. Maher, Ph.D; Beth E. Shubin Stein, M.D (Elsevier, 2024)
Purpose: To characterize the ability of the intact medial patellofemoral ligament (MPFL) and the adductor transfer and adductor sling MPFL reconstruction techniques to resist subluxation and dislocation in a cadaveric model. Methods: Nine fresh-frozen cadaveric knees were placed on a custom testing fixture with the femur fixed parallel to the floor, the tibia placed in 20° of flexion, and the patella attached to a load cell. The patella was displaced laterally, and subluxation load (in newtons), dislocation load (in newtons), maximum failure load (in newtons), patellar displacement at failure, and mode of failure were recorded. Testing was conducted with the MPFL intact and after the adductor sling and adductor transfer reconstruction techniques. Statistical analysis was completed using 1-way repeated-measures analysis of variance with the Holm-Šidák post hoc test. Results: The subluxation load was not significantly different between groups. The native MPFL dislocation load was significantly higher than the dislocation loads of both reconstruction techniques, but no significant difference between the dislocation loads of the 2 reconstruction techniques occurred. The native MPFL failure load was significantly higher than the failure loads of both reconstruction techniques. The adductor sling failure load was significantly higher than the adductor transfer failure load. The mode of failure varied across groups. The native MPFL failed by femoral avulsion, patellar avulsion, and midsubstance tear. The main mode of failure for adductor transfer was pullout, whereas failure for the adductor sling technique most often occurred at the sutures. Most of the native MPFLs and all adductor sling reconstructions failed after dislocation. The adductor transfer reconstructions were much more variable, with failures spanning from before subluxation through dislocation. Conclusions: Our cadaveric model showed that neither the adductor transfer technique nor the adductor sling technique restored failure load to that of the native condition. There was no significant difference in the subluxation or dislocation loads between the 2 MPFL reconstructions, but the adductor sling technique resulted in a higher load to failure. The adductor transfer technique frequently failed before subluxation or dislocation when compared with the adductor sling technique and the native MPFL. Clinical Relevance: The best technique for MPFL reconstruction in patients with open physes is a topic of debate. Given the long-term consequences of MPFL injury and potential for growth plate disturbance, it is important to study MPFL reconstruction techniques thoroughly, including in the laboratory setting.